The Role of Legal Education in Raising Awareness of Financial Institutions on the Prevention of Money Laundering Crime in Property Transactions - Putri Rizki Ananda; Yuli Indarsih (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Money laundering is an illegal activity that has a serious impact on the global economy. It involves the process of concealing or covering up traces of the origins of illegal funds by channelling them through legitimate financial transactions. One sector that is vulnerable to money laundering is property transactions, where criminals often use investments in property to launder their dirty money. This research will explain the role of legal education in raising awareness of financial institutions on the prevention of money laundering in property transactions. This research is a literature review that uses a qualitative approach, which implies that data will be analysed and interpreted using information and text obtained from various sources. The results of the study show that legal education plays a crucial role in raising the awareness of financial institutions on the prevention of money laundering in property transactions. This awareness is needed especially in property transactions that have a high risk of abuse and money laundering, given that they involve large sums of money and high asset values. The importance of legal education is seen through several key aspects, including understanding of the law, risk identification, legal compliance, business ethics, employee training, co-operation with authorities, and internal policy development.